Exosomes as Mediators of Cell-to-Cell Communication in Thyroid Disease - Yi Wang; Feng Xu; Jia-Yu Zhong; Xiao Lin; Su-Kang Shan; Bei Guo; Ming-Hui Zheng; Ling-Qing Yuan (International Journal of Endocrinology)
Exosomes are a type of extracellular vehicle, formed by budding cell membranes, containing proteins, DNA, and RNA. Concentrated cargoes from parent cells are enveloped in exosomes, which are cell specific and may have functions in the recipient cell, reflecting a novel physiological and pathological mechanism in disease development. As a transmitter, exosomes shuttle to different cells or tissues and mediate communications among these organelles. To date, several studies have demonstrated that exosomes play crucial roles in disease pathogenesis and development, such as breast and prostate cancer. However, studies investigating connections between exosomes and thyroid disease are limited. In this review, recent research advances on exosomes in thyroid cancer and Graves’ disease are reviewed. These studies suggest that exosomes are involved in thyroid disease and appear as impressive potentials in thyroid therapeutic areas.